Pemberian minuman secang (Caesalpinia sappan l.) terhadap kadar malondialdehid plasma dan kebugaran jasmani pada pegawai penderita prehipertensi - Farida Fitriyanti; Susetyowati Susetyowati; Mae Sri Hartati Wahyuningsih (Jurnal Gizi Klinik Indonesia, 2020)
Effect of Secang (Caesalpinia sappan L.) drink toward plasma-malondialdehyde level and physical fitness in prehypertensive government office workerBackground: Prehypertension is associated with a higher risk of hypertension and cardiovascular disease. A government office worker has lower physical activity, thus increasing the risk of hypertension, low physical fitness, and a higher level of oxidative stress. Free radical which is the product of oxidative stress can be reduced by antioxidants. Secang (Caesalpinia sappan L.) is one of the ingredients in a traditional herbal drink (jamu) and a natural source of antioxidants in the form of polyphenol.Objective: The purpose of this study is to discover the effect of secang drink supplementation, and efficacy towards plasma MDA level and physical fitness on a government office worker.Methods: This study conducted with true experimental by pre and post-test control group design. The subject is 35 prehypertensive government office workers aged between 25-45 years old in Yogyakarta, divided into treatment and control groups. Secang is given in 3.8g teabag which brewed in 200cc hot water, consumed for 4 weeks. Plasma MDA level is measured using TBARS, and physical fitness is measured using the Harvard step test. Results are analyzed using student paired t-test, Pearson and Spearman correlation test, regression test, and ANOVA.Results: There’s insignificant decrease of plasma MDA level between intervention group (from 4,28±3,16 to 3,66±1,21) and control group (4,85±2,35 to 3,65±1,33). There’s difference on Harvard step test results, intervention group increase from 35,54±20,18 to 48,09±21,86 in male, while 11,56±4,94 to 13,87±6,25 in female. In control group, male subject increase 29,20±10,06 to 38,18±23,62, but decrease 13,30±7,12 to 13,26±2,92 in female.Conclusions: 4 weeks drinks of 3.8 g Secang drink brewed in 200ml hot water, shows no evidence of lowering oxidative stress (MDA) in plasma, but it may increase physical fitness.